Group Dynamics and the Farmer Participation on Rural Agribusiness Development Program in Sematang Borang Subdistrict Palembang - Sriati Sriati; Henny Malini; Stela Wulandari (Jurnal Penyuluhan, 2020)
Abstract Rural Agribusiness Development Program (PUAP) is a program under the coordination of the National Independent Community Empowerment Program (PNPM-Mandiri), which has been carried out by the Ministry of Agriculture since 2008. PUAP is a form of facilitation of venture capital assistance for group member farmers, coordinated by the Joint Farmers Group ( Gapoktan). This study aims to: (1) measure the level of group dynamics of farmer participating in the PUAP Program, (2) measure the level of participation of farmers in the PUAP program, and (3) analyze the correlation between of farmer group dynamics with the level of farmer participation in the PUAP program in Sematang Borang Subdistrict Palembang City. This research was conducted in Sematang Borang Subdistrict, Palembang City, using the survey method (Explanatory survey). The study population was all farmers who were members of the 6 farmer groups benefiting from the PUAP program who joined the Marjasuma Gapoktan consisting of 90 farmers in the Sematang Borang District. Samples were taken proportionally stratified random (proportionate stratified random sampling), i.e. from each group were taken 4 farmers so that the total sample of 24 farmers .. Data collected included primary data and secondary data, analyzed descriptively, and the relationships between variables were analyzed by Rank Correlation Test Spearman The results showed the level of dynamics of farmer groups in Sematang Borang Subdistrict included high criteria with an average score of 33.91 (an achievement of 94.91%). Elements: group goals, group structure, task functions and group effectiveness are all high criteria. each with a score of 8.54; 8.37; 8.54 and 8.48. The level of participation of farmers belonging to farmer groups in the PUAP program is at a high criterion with an average total score of 33.25 (92.36% achievement). For each stage of participation, namely the planning, implementation, evaluation, and utilization of the results, all are included in the high criteria, each with a score of: 8.28; 8.17; 8.42; and 8.41. The level of group dynamics was positively correlated with the level of farmer participation in the PUAP Program with a correlation coefficient value of Rs = 0.80 significant at a = 0.05 Keywords: Group Dynamics, Farmer Groups, Participation, Farmers, PUAP.